Tindak Pidana Penganiayaan dalam Fiqh Jinayah dan Hukum Pidana Indonesia - Eko Wahyudi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
Often the violence perpetrated by a group of people against suspected perpetrators of certain acts of crime, sometimes even people doing things that are beyond the boundaries of humanity, called